Phase Separation: Linking Cellular Compartmentalization to Disease. Issue 7 (July 2016) - Aguzzi, Adriano; Altmeyer, Matthias
Abstract : Eukaryotic cells are complex structures capable of coordinating numerous biochemical reactions in space and time. Key to such coordination is the subdivision of intracellular space into functional compartments. Compartmentalization can be achieved by intracellular membranes, which surround organelles and act as physical barriers. In addition, cells have developed sophisticated mechanisms to partition their inner substance in a tightly regulated manner. Recent studies provide compelling evidence that membraneless compartmentalization can be achieved by liquid demixing, a process culminating in liquid–liquid phase separation and the formation of phase boundaries. We discuss how this emerging concept may help in understanding dynamic reorganization of subcellular space and highlight its potential as a framework to explain pathological protein assembly in cancer and neurodegeneration. Trends: Membraneless compartmentalization of the subcellular space occurs by liquid–liquid phase separation. Heterotypic cooperative weak interactions enable rapid rearrangements within liquid compartments. Intrinsically disordered proteins play important roles in phase transitions due to their structural plasticity and prion-like properties. Cells dynamically control the extent and duration of phase transitions. Molecular seeds such as RNA or poly(ADP-ribose) (PAR) can trigger phase transitions in a stimulus- and context-specific manner. Chaperones, disintegrase machineries, and post-translational modifications cooperate to control phase transitions. A continuum of aggregation propensities exists and cells employ an unanticipated broad range of material states in proteinaceous assemblies. These can progress into pathological aggregates associated with neurodegenerative diseases.